DIELECTRIC PROPERTIES OF ICE AT 5.1 AND 9.7GHz USING CAVITY RESONATOR - マツオカ, タケシ; フジタ, シュウジ; モリシマ, シゲノリ; マエ, シンジ; MATSUOKA, Takeshi; FUJITA, Shuji; MORISHIMA, Shigenori; MAE, Shinji (National Institute of Polar Research, 1994)
P(論文) The relative complex dielectric permittivity (ε^*=ε'-iε") of ice was investigated at 5.1 and 9.7GHz by the cavity resonator method. The purpose of the measurement was to clarify the dielectric properties, especially the loss tangent (tan δ=ε"/ε'), of ice at microwave frequencies. Because the tan δvalues of ice at microwave frequencies reported in past investigations were contradictory among several investigators by factors larger than 10,it was necessary to obtain the precise values of tan δ for application to microwave remote sensing of the cryosphere. In this study, we used the cavity resonator method, which is suitable for low loss materials such as ice. Ice samples were polycrystalline and made from deionized water. The experimental results were as follows : The values of tan δ were 1.9-2.8×(10)^<-4> at 9.7GHz and 1.5-2.5×(10)^<-4> at 5.1GHz in the temperature range -20℃ to -2℃. Thus, the values of tan δ of ice at 9.7 GHz were larger than that of ice at 5.1GHz; both of them were of the order of (10)^<-4>. It was confirmed that the values of tan δ of ice at 9.7 and 5.1GHz were not of the order of (10)^<-3> (experimental results of CUMMING (J.Appl. Phys., 23,768,1952)) but (10)^<-4> (similar to the experimental results of MATZLER and WEGMULLER (J. Phys. D : Appl. Phys., 20,1623,1987)). departmental bulletin paper